2013
DOI: 10.1039/c2cp43924g
|View full text |Cite
|
Sign up to set email alerts
|

The alanine model dipeptide Ac-Ala-NH2 exists as a mixture of Ceq7 and C5 conformers

Abstract: Microwave spectroscopy has been applied to characterize the conformations adopted in the gas phase by a small peptide derived from alanine, N-acetyl-L-alaninamide (Ac-Ala-NH(2)). This compound was vaporized by laser ablation and shown to exist as a mixture of C(eq)(7) and C(5) conformers stabilized by a CO···HN intramolecular hydrogen bond closing a seven- or a five-membered ring, respectively. The complicated quadrupole hyperfine structure originated from two (14)N nuclei has been completely resolved for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 46 publications
(6 reference statements)
8
69
0
Order By: Relevance
“…This level of theory has been found to behave satisfactorily in previous studies of several biomolecules. [7][8][9][10]12,13 The results of the calculations at the B3LYP/6-311++G(d,p) level of theory are shown in Table S1 of the ESI. †…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This level of theory has been found to behave satisfactorily in previous studies of several biomolecules. [7][8][9][10]12,13 The results of the calculations at the B3LYP/6-311++G(d,p) level of theory are shown in Table S1 of the ESI. †…”
Section: Resultsmentioning
confidence: 99%
“…Lavrich et al 6 investigated the alanine dipeptide N-acetyl-alanine N 0 -methylamide (Ac-Ala-NHMe) and observed only a C eq 7 conformation using heating methods to bring molecules into the gas phase. Very recently, the combination of FTMW spectroscopic techniques with laser ablation methods [7][8][9][10] has been successfully applied in the investigation of the conformational preferences of isolated protected dipeptides such as N-acetyl-glycinamide (Ac-Gly-NH 2 ), 11 N-acetyl-alaninamide (Ac-Ala-NH 2 ) 12 and N-acetyl-prolinamide (Ac-Pro-NH 2 ). 13 For both Ac-Gly-NH 2 and Ac-Ala-NH 2 , the molecules were found to exist as both the C eq 7 (g-turn) as well as the C 5 (b L -turn) conformation (see Scheme 1), in which the backbones are stabilized by a COÁ Á ÁHN intramolecular hydrogen bond closing a seven-or five-membered ring, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…During this complex cooling process following vaporisation, conformational isomerisations take place until the isomerisation rates fall down below the characteristic time of the expansion, freezing de facto the populations [184]. These final populations resulting from a high temperature conformational equilibrium suggest that Gibbs energies are more suitable than enthalpy at 0 K to compare with experiment, which has been supported by various examples on small molecules [186] where the distribution is correctly predicted by a room temperature equilibrium, as well as by recent work on peptides and flexible molecules [88,107,135,187,188]. These systems existing under conformations of very different entropic behaviours, e.g.…”
Section: Lessons From the Confrontation mentioning
confidence: 94%
“…They have been observed in model peptides based on Trp [63], Phe [70] and Tyr [114], but their occurrence requires specific stabilisation conditions because of the intrinsic weakness of the H-bond caused by its nonlinearity, in spite of a short H-O distance (228 pm). They are usually challenged by the other short range, but much stronger, C7 H-bonds, which lead in turn to folded backbone structures [63,70,73,83,114,188,191]. In esterified C-terminal models [46,87], the absence of an NH group forbids the folded structures.…”
Section: C5 Interactions a Signature Of Extended β-Strand-likementioning
confidence: 97%
“…Specifically, in a recent microwave spectroscopy study it was found that the alanine dipeptide populates both the C7 eq and the C5 conformations in a proportion 2:1 in the gas phase [18]. Interestingly, studies of the alanine dipeptide in vacuo are conclusive in discarding the right-handed α-helix (αR) or the polyproline II (PII) conformations as low energy minima.…”
Section: Introductionmentioning
confidence: 99%